CLASSROOM: VIDEO FOR HOMEWORK - Parveen Sarjit Sidhu (Universitas PGRI Madiun, 2020)
This action research was conducted in order to investigate the students experience and perception towards using the video making assessment approach when presenting their oral communication assessment. This was to see the impact on the students compared to presenting the traditional way in-class. Forty-five (45) respondents undertaking DUE 3012 - Communicative English 2 in Polytechnic Balik Pulau, Information Technology Department, participated in this study. The respondents had to make a video based on Chapter 1- Product and Services whereby it will be evaluated as their oral presentation assessment. A Likert Scale questionnaire was distributed and the data were tabulated using descriptive statistics. The outcome of the study was that the respondents had a positive perception towards this approach and it helped them to build their confidence level to use the English Language. Besides that, the respondents felt that this approach of assessment was successful and beneficial in helping them to understand the chapter better.